Merdeka Curriculum: Strengthening Character Through Assessment At SMP Negeri 17 Pontianak - Zuri Astari; Iwan Ramadhan (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
This research aims to determine the implementation of character strengthening through independent curriculum assessments in junior high school level education units. Curriculum changes require adjustments to the competencies of teachers and students. Especially junior high school students who have just experienced the transition from primary to junior secondary education. In order to find answers to research questions, researchers conducted research at SMP Negeri 17 Pontianak. The research method is descriptive qualitative. The research procedure was carried out starting with preparing the design, implementation and research report. Data collection techniques using observation, interviews and documentation studies. The research results were analyzed according to Milles and Huberman's analysis. Research population of teachers and students of SMP Negeri 2 Pontianak. Meanwhile, the research samples were from social studies teachers and several students. The results of the research show that SMPN 17 Pontianak is still in the adjustment or adaptation stage. Formative assessment is able to provide encouragement to teachers to be more systematic and consistent in assessing students in areas mastered. The assessment at SMPN 17 Pontianak is an evaluation for teachers to review students' abilities, for example what learning needs students need and the obstacles or challenges faced by students. Apart from still not mastering the adaptation process for teachers in the independent curriculum assessment, another obstacle is the limited number of textbooks from the central government which until now has not provided these textbooks to the SMP Negeri 17 Pontianak school. So students are forced to buy textbooks individually and not all students can buy textbooks.